2022
DOI: 10.3390/ph15070884
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanosystems Based on Nicotinate-Functionalized Mesoporous Silica and Silver Chloride Nanoparticles Loaded with Phenytoin for Preventing Pseudomonas aeruginosa Biofilm Development

Abstract: Pseudomonas aeruginosa (PA) is one of the most common bacteria isolated from chronic wounds and burns. Its treatment is a challenge due to antimicrobial drug resistance and biofilm formation. In this context, this study aimed to perform the synthesis and full characterization of hybrid nanosystems based on mesoporous silica nanoparticles (MSNs) functionalized with a nicotinic ligand and silver chloride nanoparticles, both phenytoin sodium (Ph)-loaded and unloaded, to evaluate the antibacterial properties again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…As can be seen in Table 5 , after PTN encapsulation in the material, the MIC and MBC values decreased considerably due to the additive effect between PTN and silver when at least 2 dilutions of the material used is considered. These results were even better than those previously reported by our group for a similar system [ 38 ]. Importantly, the release of PTN in physiological medium was studied on the 1-Ag@PTN material (see Figure S10 ).…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…As can be seen in Table 5 , after PTN encapsulation in the material, the MIC and MBC values decreased considerably due to the additive effect between PTN and silver when at least 2 dilutions of the material used is considered. These results were even better than those previously reported by our group for a similar system [ 38 ]. Importantly, the release of PTN in physiological medium was studied on the 1-Ag@PTN material (see Figure S10 ).…”
Section: Resultscontrasting
confidence: 69%
“…Therefore, silver materials were shown to inhibit the growth of S. aureus and P. aeruginosa , which are predominant in chronic wounds and burns [ 50 , 51 ]. The effect of phenytoin sodium encapsulation in the 1-Ag material (yielding 1-Ag@PTN ) on wound tissue regeneration was also analyzed, since previous studies showed that silver and phenytoin sodium activities against P. aeruginosa [ 38 ] are additive. The MIC and MBC values of 1-Ag@PTN against the three strains of P. aeruginosa were estimated and are listed in Table 5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system showed a promising antibacterial activity against three different planktonic P. aeruginosa strains. These strains are known to have a great facility for generating biofilms; however, the treatment of this silica system obtained very good results in terms of minimal biofilm inhibitory concentration (MBIC) and minimal biofilm eradication concentration (MBEC) values compared to silver NPs alone [120]. Regarding systems based on silica and silver complexes, to the best of our knowledge, to date there is only a single paper by Y. Kuthati et al that reported the preparation of IBN-4 type silica by hydrothermal treatment, loaded with a silver complex via the reaction with a pH-sensitive hydrazone ligand.…”
Section: Silvermentioning
confidence: 99%
“…In Table 7 , although Sulfamoxole has not been verified in the database, relevant work [ 49 ] has demonstrated its inhibitory activity against E. coli . Similarly, in Table 8 , there is also studies [ 50 , 51 ] proving that Biphenyl and Phenytoin drugs have antibacterial activity against P. aeruginosa . In summary, the proposed model can indeed discover the potential response of microbes to drugs, thereby promoting new treatment options.…”
Section: Experiments Resultsmentioning
confidence: 78%